(untitled) (Journal of Universal Science Research, 2023)
This article denotes about the work of Ernest Hemingway and his contribution to the literature as well as about the play of “Whom the bell tolls”. There is a brief information about it, how Hemingway depicted the hero, main features of his heroism in his work. Moreover, this article describes how the war influenced to the work of Hemingway, in which his portrayal of heroism has had a significant impact on literature and society, challenging traditional notions of heroism and inspiring readers to seek their own meaning and purpose in life.